Physicians’ Perceptions and Suggestions for the Adaptation of a US-Based Serious Illness Communication Training in a Non-US Culture: A Qualitative Study - Onishi, Eriko; Nakagawa, Shunichi; Uemura, Takeshi; Shiozawa, Youkie; Yuasa, Misuzu; Ito, Kaori; Kobayashi, Yuki; Ishikawa, Hirono; Ouchi, Kei (Journal of pain and symptom management, 2021)
US-based serious illness communication training pedagogy has not been well studied outside of the United States. To explore the perception of a US-based, serious illness communication training pedagogy in a non-US culture and to identify aspects requiring cultural adaptations. In September 2019, we conducted a qualitative study using convenient sampling at two urban, academic medical centers in Tokyo, Japan. Semistructured interviews were conducted to Japanese physicians who participated in the four-hour VitalTalk training in Japanese. We explored six majored themes: 1) global impression of the training; 2) main goals from participation; 3) appropriateness of didactics; 4) role play experiences; 5) take away points from the training; and 6) changes in their own communication practice after the training. Interviews were transcribed, coded, and analyzed using phenomenological approach. All 24 participants found the VitalTalk pedagogy novel and beneficial, stressing the importance of demonstrating empathy, reflecting on own skills, and recognizing the importance of feedback that emphasizes the use of specific words. Participants also pointed out that Japanese patients generally do not express their strong emotions explicitly. Our study found empirical evidence that the VitalTalk pedagogy is perceived to be novel and beneficial in a non-US cultural setting. Cultural adaptations in expression and response to emotion may be required to maximize its efficacy in Japan. To meet the needs of clinical practice in Japan, further studies are needed to empirically test the suggested refinements for the VitalTalk pedagogy.